Implementation of Child-Friendly Schools (SRA) at MIN 2 Nagan Raya: An Implicative Analysis of the Internalization of Noble Morals - Nurmanzili (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the implementation of the Child-Friendly School (CFS) Program at MIN 2 Nagan Raya and its implications for the internalization of students' noble morals. Child-Friendly Schools are an educational approach that emphasizes the protection of children's rights, the creation of a safe, inclusive, and violence-free learning environment, and active student participation in the learning process. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions according to the Miles and Huberman model. The results show that the implementation of CFS at MIN 2 Nagan Raya has included the habituation of positive behavior, strengthening harmonious relationships between teachers and students, and the integration of character values in learning activities. However, several obstacles were found, such as unequal understanding among educators, limited physical facilities that support children's comfort, and the persistence of verbal violence practices. This study recommends the need for intensive training for educators regarding the CFS concept, improvement of infrastructure, and strengthening synergy between schools, parents, and the community in creating an educational environment that supports the formation of students' noble morals.